Analisis Penggunaan Pronomina Persona sebagai Penyapa dan Pengacu - Adhani, Agnes (Widya Warta, 2014)
This study tried to answer three questions, namely (1) what are the forms of personal pronoun used to address and to refer to?, (2) what are the factors which influence the use of personal pronoun to address and to refer to?, and (3) what are the degrees of intimacy between the speaker and the listener in the use of personal pronoun to address and to refer to? The research is qualitative-descriptive in nature. It is based on 60 utterances taken from short message services (SMS), BlackBerry Messagers (BBM), and writings in accounts or comments in facebooks. The result of the research indicated that (1) personal pronoun used (a) to address is the second personal pronoun - singular and plural and (b) to refer to is the first personal pronoun - singular and plural as well as the third personal pronoun - singular and plural, (2) the factors influencing the use of personal pronoun to address and to refer to in 10 communicative acts include (a) social environment, (b) local language, and (c) national culture concerning courtesy, and (3) the degrees of intimacy between the speaker and the listener comprise four - (a) intimate, (b) respectful, (c) neutral, and (d) respectful-intimate.